2021
DOI: 10.3389/fpsyg.2021.775804
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Basic Psychological Needs, Motivation, and Vitality Before and During COVID-19: A Self-Determination Theory Approach

Abstract: Self-determination theory assumes that the basic psychological needs for autonomy, competence, and relatedness are associated with motivational regulation. As these basic psychological needs may have been affected by the shift to distance learning, students’ motivational regulation and vitality may have suffered as well. The purpose of this study was to examine the motivational regulation, satisfaction, or frustration of the basic psychological needs and vitality of university students before and after the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 79 publications
2
24
0
4
Order By: Relevance
“…As evident in other SDT-based studies (Müller et al, 2021;Vandenkerckhove et al, 2019), external regulation is less well explained by perceived satisfaction of the basic needs. However, the explanatory content is higher than in the data collected before the shift to online learning.…”
Section: Summary and Discussionmentioning
confidence: 65%
“…As evident in other SDT-based studies (Müller et al, 2021;Vandenkerckhove et al, 2019), external regulation is less well explained by perceived satisfaction of the basic needs. However, the explanatory content is higher than in the data collected before the shift to online learning.…”
Section: Summary and Discussionmentioning
confidence: 65%
“…This study provides relevant findings, in line with the well‐established SDT (Ryan & Deci, 2017 ), about the essential role of basic psychological needs for psychological well‐being in times of uncertainty (Vermote et al, 2021 ). The reduction in need satisfaction after the lockdown in Italy could presumably be due to a decreased opportunity to choose activities, to be physically connected to others, and to feel effective at university or work and confirm the higher level of need frustration in the academic context during the distance learning period than before the COVID‐19 pandemic (Müller et al, 2021 ). Furthermore, the implementation of the home confinement restrictions exposed the population to the beginning of a health crisis, creating concern and uncertainty that could decrease the perception of need satisfaction (Vermote et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
“…However, several researchers have found students’ motivation to decline across different developmental phases and time spans (e.g., Benden & Lauermann, 2021; Jacobs et al, 2002; Kosovich et al, 2017; Robinson et al, 2019). In online courses during pandemic-related lockdowns, motivation was possibly threatened more because many prerequisites for motivation were missing (e.g., social presence and interaction; see also Müller et al, 2021) and students reported an increased amount of stress (Usher et al, 2021). The question arises as to what differences emerge in students’ motivation during distance learning compared to face-to-face learning.…”
Section: Student Motivationmentioning
confidence: 99%